Alternatif Mengembangkan Kemampuan Motorik Kasar Anak Usia Dini Dengan Aktivitas Akuatik (Berenang) - Febrianta, Yudha (AL-ATHFAL : JURNAL PENDIDIKAN ANAK, 2016)
Early childhood is the golden age that have just come onces in a lifetime and can not be repeated. At that time the child is specifically easy to receive various stimuli from the surrounding environment. The development of the child occurring since the age of 0-4 years old of the same magnitude with the developments in the age of 4-8 years. Swimming is a sport that involves all the muscles in all parts of the body. Water sports also launched vital organs such as the heart and lungs to trained in accordance with their performance. Because swimming makes the muscles of the chest and lungs inflate and create the capacity the greater. So that supports the ability of physical or motor development of children to be good. As for the benefits of swimming in early childhood, among others, the following : (a) Increase IQ, (b) Easy to learn, (c) high endurance, (d) Forming kepribadaian, (e) Establish a close relationship with the child, (f) Provide stimulation on the motor, (g) to Train self-confidence and courage of the child, (h) Train the social skills of the child, (i) Accelerating growth , (j) Trains the sense of balance, (k) used to the water, (l) Assist the development of terms, (m) That are not easily surprised, (n) So not fussy at bath, (o) Assist the adaptation of the baby in another place, (p) Help the child to think, learn and problem solving, (q) the Means of expression of the child.